ABIN1 dysfunction as a genetic basis for lupus nephritis (2013)
The genetic factors underlying the pathogenesis of lupus nephritis associated with systemic lupus erythematosus are largely unknown, although animal studies indicate that nuclear factor (NF)-?B is involved. We reported previously that aknockin mouse expressinganin active form of ABIN1 (ABIN1[D485N]) develops lupus-like autoimmune disease and demonstrates enhanced activation of NF-?B and mitogen-activated protein kinases in immune cells after toll-like receptor stimulation. In the current study, we show that ABIN1[D485N] mice develop progressive GN similar to class III and IV lupus nephritis in humans. To investigate the clinical relevance of ABIN1 dysfunction, we genotyped five single-nucleotide polymorphisms in the gene encoding ABIN1, TNIP1, in samples from European-American, African American, Asian, Gullah, and Hispanic participants in the Large Lupus Association Study 2. Comparing cases of systemic lupus erythematosus with nephritis and cases ofsystemic lupus erythematosus without nephritis revealed strong associations with lupus nephritis at rs7708392 in European Americans and rs4958881 in African Americans. Comparing cases of systemic lupus erythematosus with nephritis and healthy controls revealed a stronger association at rs7708392 in European Americans but not at rs4958881 in African Americans. Our data suggest that variants in the TNIP1 gene are associated with the risk for lupus nephritis and could be mechanistically involved in disease development via aberrant regulation of NF-?B and mitogen-activated protein kinase activity. Copyright © 2013 by the American Society of Nephrology.